Vermicomposting A viable option for organic nutrients in Sikkim - Kalita, H; Babu, S; Kishore, K; Singh, R; Yadav, G S (Indian Farming, 2016)
Vermicomposting is a valuable source of nutrients for organic agriculture by utilizing the farm wastes and it may also be a highly profitable venture to the farmers for securing their livelihoods, because, with at, it is possible to earn up to Rupees 1 lakh annually by maintaining a unit of 3 tonnes capacity.